2019
DOI: 10.1371/journal.pone.0226240
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the gut microbiota in professional martial arts athletes: A comparison between different competition levels

Abstract: Recent evidence suggests that athletes have microbial features distinct from those of sedentary individuals. However, the characteristics of the gut microbiota in athletes competing at different levels have not been assessed. The aim of this study was to investigate whether the gut microbiome is significantly different between higher-level and lower-level athletes. Faecal microbiota communities were analysed with hypervariable tag sequencing of the V3–V4 region of the 16S rRNA gene among 28 professional martia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
3
31
0
2
Order By: Relevance
“…Furthermore, in our study, the relative abundance of Ruminoccoccus was found to be higher in subjects with a lower level of adherence to MD, and this is in line with the work of Martinez-Medina et al, showing an association between this genus and the consumption of a diet rich in saturated fat and sugars [43]. The Megasphaera genus was found to be more abundant in low-active subjects, in accordance to the findings from Liang et al, who reported a higher abundance of this genus in lower-level athletes in comparison with higher-level ones [40]. The higher abundance of Lachnobacterium in low-active participants is a novel observation that needs to be explored in depth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, in our study, the relative abundance of Ruminoccoccus was found to be higher in subjects with a lower level of adherence to MD, and this is in line with the work of Martinez-Medina et al, showing an association between this genus and the consumption of a diet rich in saturated fat and sugars [43]. The Megasphaera genus was found to be more abundant in low-active subjects, in accordance to the findings from Liang et al, who reported a higher abundance of this genus in lower-level athletes in comparison with higher-level ones [40]. The higher abundance of Lachnobacterium in low-active participants is a novel observation that needs to be explored in depth.…”
Section: Discussionsupporting
confidence: 90%
“…Lachnospira among Firmicutes, so as Prevotella among Bacteroidetes, seem to be involved in the fermentation of fibers, leading to a higher SCFA production. Even if the abundance of Firmicutes is generally associated with a higher intake of animal-associated foods, several members of this phylum were associated with SCFA production and were reported to be more abundant in individuals with higher adherence to the MD patterns and higher consumption of vegetables [17,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…We included studies that compared microbiota composition and diversity of individuals from different sporting disciplines [45,48,[52][53][54][55]: (a) some disciplines were strongly associated with a relative abundance of bacteria as described in Table 1 [52]; (b) athletes from distinct disciplines and level of competition displayed significative differences in microbiota diversity and species richness [48,54]; and (c) high-performing individuals have been reported with a greater abundance of the genera Parabacteroides, Phascolarctobacterium, Oscillibacter, Bilophila and a lower abundance of Megasphaera [54].…”
Section: Gut Microbiota Composition In Studies Involving Athletesmentioning
confidence: 99%
“…Conversely, the abundant genus Megasphaerain the lower-level athletes (which has been suggested to be more abundant in chronic inflammatory diseases, such as nonalcoholic steatohepatitis and genital tract inflammation), has the potential to produce high levels of LPS [ 176 , 177 ]. Furthermore, the analysis of the functional prediction revealed that histidine and carbohydrate metabolism pathways were markedly overrepresented in the gut microbiota of higher-level athletes [ 178 ].…”
Section: Studies In Humansmentioning
confidence: 99%